The Impact of Taking into Account Information Asymmetries and the Credit Market Structure in the Assessment of Borrowers' Credit Worthiness: Case of Tunisia - Marzouki, Mohamed Miras; Yemmen, Jihene (Journal of Reviews on Global Economics, 2023)
We attempt to assess borrowers’ credit worthiness in three scenarios one heralding prevalence of information asymmetries the second heralding absence of information asymmetries and the third a realistic scenario encompassing both features for the sake of determining which one gives the best outcome in terms of goodness of fit and adequacy of the model specification with the corresponding market structure of the credit market in purview. The added value of this research is that, when we want to estimate any entity, the explanatory variables carrying market imperfections must be manifested and not implicitly invocated because of the endogeneity of market imperfections and the market structure should be specified clearly; otherwise, the estimation is inadequate and the empirical results do not correspond to the theoretical predilections. In other words, the conformity of empirical results with theoretical predilections does not rely on the absence of information asymmetries, whose full recognition does not introduce spuriousness into empirical results. The research is a comparative cross investigation of scenarios highlighting the best fit to borrowers' Creditworthiness assessment and deducing through logical analysis the role payed by information asymmetries and the banking market power in shaping this fit.